Active and selective reverse water-gas shift reaction over Pt/Na-Zeolite catalysts. (December 2022) - Seo, Jeong-Cheol; Park, Gyungah; Arshad, Malik Waqar; Zhang, Chundong; Kim, Sungtak; Kim, Seok Ki
Abstract: The introduction of the frustrated Lewis pair (FLP) concept in heterogeneous catalysis, particularly zeolites, is effective in activating stable molecules, such as CO2 . However, regulating the FLP density structure to control the activity and selectivity remains challenging. This study examined the effects of the FLP density and zeolite structure on the reverse water-gas shift reaction using Pt/zeolite catalysts. The reaction results obtained using catalysts with various zeolites showed that the presence of FLP in the zeolite promoted CO2 conversion and CO selectivity, but a high FLP density was not necessarily beneficial. A high density of FLP could delay the intracrystalline diffusion of intermediates and could lower the CO selectivity. Operando infrared spectroscopy and density functional theory calculations suggested that FLP could effectively stabilize the intermediate responsible for CO production through selective hydrogenation of the oxygen atom of CO2 at the initial stage of the reaction. Graphical Abstract: ga1 Highlights: Frustrated Lewis pair activates CO2 hydrogenation to CO. H-exchanged zeolite preferably produced CH4 than CO. CO selectivity was increased by facilitating intracrystalline mass-transfer property. Na-exchanged zeolite Y with Pt showed excellent CO production.